3D kinematic analysis of the front handspring stepout: a pilot study - Penitente, G.; Merni, F. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
This study analyzes the 3D kinematics of the front handspring stepout (FHS) performed by three female gymnasts with different levels of expertise. The purpose was to identify the crucial biomechanical components and how they govern the performance of the athletes. An optoelectronics system (with 6 infrared cameras at 100 Hz) was used to record a specific passive marker-set placed on the subjects bodies. We found that the most important biomechanical parameters were the horizontal components of displacement and velocity.